Mission Possible - The Mission on Climate Neutral and Smart Cities A new approach to sustainable urban transformation and urban transition to climate neutrality - Chrysses Nicolaides (Renewable Energy and Sustainable Development)
Europe is taking the lead in the urban transition to climate neutrality to strengthen its role as a global driver of sustainable growth, creating synergies between European and international climate initiatives and stakeholders. The Mission on Climate Neutral and Smart Cities is a challenging and ambitious endeavor where cities commit to a new form of sustainable urban transformation for the benefit of quality of life and sustainability. The European Green Deal announced by the European Commission will transform the EU into a modern resource efficient and competitive economy and is the strategy through which to achieve EU climate neutrality by 2050. Cities have the potential to lead the efforts to deliver on the European Green Deal, because they produce about 72% of all global greenhouse gas emissions although cities cover about 3% of the land on Earth.  Moreover, cities are growing fast and in Europe, it is estimated that by 2050 almost 85% of Europeans will be living in cities. Therefore, the climate emergency must be tackled by cities and by citizens. This is the rationale behind the work of the EU Mission Board on Climate Neutral Cities and after consultations with citizens all over Europe the Mission Board proposes the following mission: “100 climate neutral cities by 2030 - by and for the citizens”. The main objective of the proposed Mission is to support, promote and showcase 100 European cities in their systemic transformation towards climate neutrality by 2030. The mission would make these cities into experimentation and innovation hubs for all cities, thus leading on the delivery of the European Green Deal and on Europe’s efforts to become climate neutral by 2050. To achieve in ten years what Europe plans to achieve in 30 years is a huge challenge that requires a systemic transformation of European cities. This is urgent and necessary for acting on the global climate emergency and for delivering co-benefits that will create better jobs and enhance people’s well-being. It is also feasible with the availability of technologies and innovative solutions for sustainable energy, transport, food, water and material systems. Climate neutrality is achieved by reducing greenhouse gas emissions as much as possible and compensating for any remaining emissions. The transition to a net-zero emissions society requires action on all fronts such as; energy, transport, mobility, buildings, and shifting towards greener, digital and circular economies. The Mission considers and deals with the international dimension as climate neutrality is a global problem that requires international dialogue and cooperation.  Although the focus is on the intra-European content and setup of the mission, the issue of the international outreach of the mission is considered a priority, to facilitate and create synergies between European and international climate initiatives and stakeholders – academia, business and citizens. The international dimension of the Mission is also characterised by its contribution to the UN Agenda 2030 for Sustainable Development that provides a global policy framework for ending all forms of poverty, fighting inequalities and tackling climate change in a socially inclusive manner. A holistic and transformative mission for climate neutral cities, based on citizen participation and social inclusiveness, can contribute and help EU progress towards multiple Sustainable Development Goals (SDGs). The approach to cities’ climate-related challenges is at the core of SDG 11 - “Sustainable Cities and Communities” and contributes significantly to other SDGs such as “Good Health and Well-Being”, “Decent Work and Economic Growth” and “Affordable and Clean Energy”. In this respect and as energy production and use is currently responsible for 75% of EU greenhouse gas emissions, energy consumption in all its forms needs to be reduced, especially in urban areas where consumption is highest. Cities are encouraged to connect to international networks in order to accelerate learning, replicability and scaling-up of solutions through sharing of good practices and joint actions and ultimately serve as an inspiration for cities across the world.